Food paste production from pre-fried harton plantain residues (2017)
The goal of this study was to evaluate the use of harton plantain pre-fried residues (HPPR) that result from the patacon’s manufacture, and that represent, in average, 30 % ofthe mothly losses. Given the high perishability of these residues, a well—accepted product with longer endurance that facilitate the sub-product management was formulated. Three different brands of wheat flour and semolin were used to evaluate the lowest flour enclosed in the paste manufacture. The water absorption and loss tests showed that the best mixture contained 65 % of HPPR and 35 % of semolina. Sensory tests with consumers helped in the seIection of this formulation. The texture analysis showed that the diy pasta of HPPR is more fragile and less firm than a standard paste, but throughout cooking it remained stable and presented good consistency.